3D cell culture models and organ‐on‐a‐chip: Meet separation science and mass spectrometry. Issue 1 (30th September 2019) - Lin, Ann; Sved Skottvoll, Frøydis; Rayner, Simon; Pedersen‐Bjergaard, Stig; Sullivan, Gareth; Krauss, Stefan; Ray Wilson, Steven; Harrison, Sean
Abstract: In vitro derived simplified 3D representations of human organs or organ functionalities are predicted to play a major role in disease modeling, drug development, and personalized medicine, as they complement traditional cell line approaches and animal models. The cells for 3D organ representations may be derived from primary tissues, embryonic stem cells or induced pluripotent stem cells and come in a variety of formats from aggregates of individual or mixed cell types, self‐organizing in vitro developed "organoids" and tissue mimicking chips. Microfluidic devices that allow long‐term maintenance and combination with other tissues, cells or organoids are commonly referred to as "microphysiological" or "organ‐on‐a‐chip" systems. Organ‐on‐a‐chip technology allows a broad range of "on‐chip" and "off‐chip" analytical techniques, whereby "on‐chip" techniques offer the possibility of real time tracking and analysis. In the rapidly expanding tool kit for real time analytical assays, mass spectrometry, combined with "on‐chip" electrophoresis, and other separation approaches offer attractive emerging tools. In this review, we provide an overview of current 3D cell culture models, a compendium of current analytical strategies, and we make a case for new approaches for integrating separation science and mass spectrometry in this rapidly expanding research field.